THEORETICAL APPROACHES TO CYBERSECURITY IN THE ERA OF HYBRID WARFARE (International journal of artificial intelligence, 2026)
At present, as a result of the transformation of international relations, traditional military confrontations are increasingly being replaced by multifaceted hybrid wars, which makes the protection of the digital dimension of state sovereignty a priority task. This article analyzes the negative impact of cyberattacks on state security, political stability, and national infrastructure using examples from the contemporary geopolitical environment. In the course of the study, particular attention is paid to ensuring the inviolability of digital borders under conditions of hybrid threats and to strengthening the legal foundations of the concept of “cyber sovereignty ”. The author puts forward scholarly hypotheses suggesting that the intensification of interstate competition in cyberspace may lead to a crisis of international legal norms. The article concludes with practical recommendations aimed at countering hybrid warfare through the modernization of national cybersecurity systems and the enhancement of international cooperation.